A REFEIÇÃO EUCARISTICA COMO MARCA IDENTITÁRIA E PERTENÇA RELIGIOSA NA COMUNIDADE CRISTÃ DE CORINTO - FREDERICO, DANIELLE LUCY BÓSIO (2019)
“Food is good to think about,” says Claude Lévi-Strauss, who through food seeks to discern the societies and groups around the plate. Variations on this theme may indicate from social hierarchies, access to food to what lies beyond. Having as an instrument the anthropology of food and the “hermeneutics of spaces”, we seek a better understanding of the block in 1 Co-rinthians 8 to 11, which has as its central theme some types of meals that were present in Greco-Roman tables and also in Christian community in formation in the city of Corinth. This first-century community, mostly made up of people from the lower strata, seeks, in the act of eating together, to establish proximity, cohesion and the creation of its own identity in front of the numerous religious groups existing in the period. To this end, the communal meal and the Eucharistic ritual, structured as a funeral meal, seek, among other things, the preservation of memory and the participation of the risen Christ, a new deity established and celebrated by the members of this apostle-led community of faith Paul. As ritual food, its performance needs to occur precisely in order to achieve its intended goal. This question was not being ob-served by the members of this Christian group, causing the apostle to recall the traditions as well as the institution of the Eucharistic ritual, so that it could be properly performed. These community meetings could take place in various venues, such as shops, domus and insulae, and there is not necessarily a pre-established fixed venue for them. We understand that these meetings mostly took place in the insulae, given the popular character of the Christian com-munity, and that these meetings should be itinerant. In them the food frugality was evident and the ritual, established with the elements of bread and wine, was present and possible. The living presence of the new deity, the meal's honoree, would have his life and teachings shared at the table, so that new people would have access to this new religion in formation. Food, therefore, is good for thinking and also for creating identity, as it was recognized as a structur-ing element in the medium-world for both the living and the dead.